Os efeitos da desinformação durante a Pandemia de Covid-19 em grupo de whatsapp - Sousa, Necilma Macêdo de (2024)
It presents an analysis of the dissemination of the effects of disinformation popularly known as Fake News, in the case related to Covid-19, during the pandemic in a WhatsApp group, as a product of post-truth. The problem issue lies in the way the group elaborates the reception and dissemination of false information, and perceiving them, how and why do they disseminate them? And it is justified as an informational study about practices that focus on ethical value agendas, both the information conveyed and the relationships established in the pandemic period in digital environments. In view of this, Fake News in relation to Covid-19 is the subject, since these when disseminated represented a risk to people's lives. Thus, the general objective is to analyze the consumption and dissemination of Fake News, the implications and relevance of these informational exchanges for the WhatsApp group, with a view to the establishment and promotion of information and its exercise in fostering citizen practice when producing, disseminate and identify Fake News, as a product of post-truth. In this sense, the following specific objectives are pursued: a) To know the process of reception and dissemination of Fake News in the WhatsApp group and its flows, during the Covid-19 pandemic; b) Identify the information needs of the subjects of the WhatsApp group; c) List some effects of the consumption, production and dissemination of false messages about Covid-19. The research is characterized as a case study of a descriptive, field, and exploratory with a qualitative approach. Uses Bardin's Content Analysis as an analysis procedure. The results showed that there was an intense flow of dissemination of Fake News related to Covid-19 in the group studied. In view of the proposed objectives, concepts were listed that led to knowing the process of dissemination of Fake News and its flows in the WhatsApp group, and the identification of the information needs of the subjects identified in the study, and also to examine the situational and affective cognitive aspects related to literacy and competence in information, relating some effects of consumption, production and dissemination of messages about Covid-19 in the group. It is concluded that the term Fake News is a cybercrime and that it encompasses a terminological variable that generates informational error or mistake, sometimes with a view to financial profit or political advantage over other consumers of this type of message.